Response of thin walled metallic structures to underwater explosion: A review - Nagesh; Gupta, N.K. (International journal of impact engineering, 2021)
•Review of salient published works on load characterization and structural response of thin walled plated structures subjected to UNDEX. Review also entails comparative plot of non-dimensional experimental response of thin walled circular and rectangular plates subjected to submerged explosive charge against extensive experimental results for incident impulsive blast loads, with an objective to assess the consistency of results of UNDEX experiments by various authors.•Key aspects of UNDEX phenomenon along with load characterisation on a waterborne structure including Fluid Structure Interaction (FSI) effects presented.•Salient features in numerical modelling of UNDEX loading and simulations of associated highly non-linear structural response with increasing intensity of Shock Factor discussed.•Various simple and complex phenomenological damage models in conjunction with the discussed numerical modelling approach, relevant in the simulations of observed failure modes highlighted.•Effective approach towards numerical simulations of structural response under UNDEX based on various simple uncoupled damage models and the involved failure / damage parameters to be calibrated, discussed in detail. The paper reviews some salient research works on load characterization and structural response of thin walled metallic structures subjected to Underwater Explosion (UNDEX), while highlighting the critical gaps and scope for further research work. The key aspects of an UNDEX phenomenon including Fluid Structure Interaction (FSI) and loading mechanisms on air backed fully submerged structures has been elucidated. Expressions for estimation of an early time far field UNDEX loading history on a plated structure considering FSI effects based on Taylor's theory, have been presented. With an objective to assess the consistency of published results and categorization of observed failure modes in UNDEX experiments, a composite plot of displacement response of clamped circular and rectangular plates in comparison to the response trends for impulsive blast loads have been presented. The comparisons presented in terms of non-dimensional parameters bring out the need and significance of more UNDEX experiments. Salient aspects in numerical modelling of UNDEX loading with increasing Shock Factor and simulations of associated highly non-linear structural response and experimentally observed ductile fracture modes have also been discussed. Various simple and complex phenomenological damage models, relevant in the numerical simulations of observed failure and fracture modes have been highlighted, with an emphasis on simple uncoupled strength models, which are relatively simple to calibrate. Approach towards FEA numerical simulations of UNDEX structural response using simple uncoupled damage models, including calibration of involved failure parameters, has been discussed in detail.